AN ANALYSIS OF PERLOCUTIONARY SPEECH ACTS USED BY THE MAIN CHARACTER ON WISH DRAGON MOVIE - Anam, Asroful; Andayani, Sri; Wafa, Hosnol; Mulyono, Sugeng Edy; Hidayati, Nuril (JURNAL LITERASI, 2024)
This research analyzes the perlocutionary speech acts used by the main character in the film Wish Dragon. This research uses the pragmatic theory of perlocutionary speech acts. The method used in this research is the qualitative description analysis method from Sudaryanto's theory, while to search or collect data and analyze this research data using George Yule's theory. The results found show that the data found in this research are 13 types which are included in perlocutionary from the 83 data found in the wish dragon film. 2 data were used to criticize, 10 data were used to greeting, 5 data were persuade, 9 data were used to thank you, 13 data were used to scoffed, 5 data were used to say goodbye, 4 data were blame, 13 data were apologize, 2 data were complain, 5 data were rejection. , praise shows 9 data, satirize shows 3 data, and angry shows 3 data.